Analisis Faktor-Faktor Yang Mempengaruhi Kebijakan Dividen Pada Perusahaan LQ45 Di Bursa Efek Indonesia - Abd. Rahman Shaleh; Diana Dwi Astuti; Agustin Hari Prastyowati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2021)
The purpose of this study is to analyze the effect of size, profitability, maturity, insider ownership and leverage on dividend policy using the LQ45 company object listed on the Indonesia Stock Exchange (IDX). This research was conducted for five consecutive years from 2015 to 2019 which included 27 sample companies taken using purposive sampling technique. The data were analyzed using multiple linear regression analysis. The results showed that the size, maturity and insider ownership variables partially had an insignificant effect on dividend policy, while profitability and leverage had a significant effect on dividend policy. Simultaneously, size, profitability, maturity, insider ownership and leverage had a significant effect on dividend policy.